1986
DOI: 10.3354/meps029061
|View full text |Cite
|
Sign up to set email alerts
|

Development, growth, and survivorship of the copepod Calanus marshallae in the laboratory

Abstract: Development times from egg to adult Calanus marshallae (Copepoda, Crustacea) were 36 d at 15 'C, 62 d at 11 "C and 64 d at 10 'C. Stage-by-stage development was not isochronal but followed a sigmoidal pattern. Egg, NI and N2 together took 3.4 d at 10 "C (= 5.3 % of the total development time). N3 had the second longest duration of any stage (6.8 d at 10 "C; 10.7 % of total development). Stage duration decreased from N3 through N6, with N6 having the shortest duration of any stage (2.6 d), then development beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 16 publications
5
64
1
Order By: Relevance
“…maturity). We calculated the median development time from the regression of the percent copepodites or adults in the cohort versus days (Peterson, 1986). The size at maturity and somatic growth were determined using prosome length measurements (after about the C-IV stage copepod sex could be determined and only female sizes were measured).…”
Section: Analysis Of Life-history Datamentioning
confidence: 99%
See 1 more Smart Citation
“…maturity). We calculated the median development time from the regression of the percent copepodites or adults in the cohort versus days (Peterson, 1986). The size at maturity and somatic growth were determined using prosome length measurements (after about the C-IV stage copepod sex could be determined and only female sizes were measured).…”
Section: Analysis Of Life-history Datamentioning
confidence: 99%
“…We employed the Statview Ò version 5.0.1 software for all statistical analyses. To determine the age to maturity and life-stage duration, we used the median development time (Peterson, 1986;Carlotti and Nival, 1991), which is defined as the age, x, at which 50% of the individuals reached a specific stage (e.g. maturity).…”
Section: Analysis Of Life-history Datamentioning
confidence: 99%
“…The major factors relevant to growth and development of nauplii include initial egg characteristics, temperature, food concentration and the type of food consumed by the nauplii. The initial egg characteristics result from the past feeding of the females producing the eggs (Peterson 1986, Guisande & Harris 1995, Melle 1998). …”
Section: Introductionmentioning
confidence: 99%
“…data), so the variation we document here cannot be explained solely by heritable genetic differences (McLaren and Corkett 1978). Peterson (1986) found that families of Calanus marshallae that developed rapidly to one stage did not always maintain this lead. Although some of the individuals we followed showed a similar pattern, there were consistently rapid or slow developers among individuals, and mean instar durations or development times mask a great deal of interesting, persistent individual variation that has direct consequences for understanding lifehistory ecology and population dynamics.…”
mentioning
confidence: 99%
“…Miller et al 1984;Peterson 1986). Median development time to a specific stage is then estimated as the time when 50% of the population has molted to that stage.…”
mentioning
confidence: 99%